Leader-Follower Formation Control Of Quadrotors With Collision Avoidance Using Artificial Potential Field - Ahmad Rasdan Rosdi; Noor Hanis Izzuddin Mat Lazim; Muhammad Muaz Abni Hajar; Liyana Ramli (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.